224 One-Year Outcomes in Patients with Colorectal Malignancy and Low Functional Capacity on CPET. (19th August 2022) - Tay, Tricia; Ryska, Ondrej; Johnson, T
Abstract: Aim: Many patients with colorectal carcinoma (CRC) undergo Cardio-Pulmonary Exercise Test (CPET) to risk-stratify their suitability for surgery. This study aims to evaluate the 1-year outcomes of patients with colorectal malignancy and low functional capacity on CPET. The secondary aim is to evaluate the correlation between P-/CR-POSSUM scores and one-year outcomes. Method: All patients with stage I-IIICRC who underwent CPET between January 2013-August 2020 with Anaerobic Threshold (AT)<10ml/min/kg follow-up for one year were included. Major complications were classified using Clavien-Dindo classification of Grade III or higher. Results: We included 77patients(64%males) with median age of 77(range 53–90). Thirty-one patients received best supportive care;46 underwent elective resection with median AT of 7.9(5.3–9.5)ml/min/kg and 8.7(6.4–9.9)ml/min/kg respectively(p=0.001).Of those treated surgically, 9(20%)had major complications. There was no 30-day mortality. Median postoperative length of stay (LOS) was 8(3–42) days. Median overall survival(OS) among patients with surgery versus best supportive management was longer–42(8–106)months vs.25(2–59)months(p<0.0001).1-year survival rate was higher-57%vs.19%(p=0.002)in patients who had surgery compared to those with non-surgical management. Presence of major complications correlates with AT(p=0.003), LOS(p=0.007), OS(p<0.0001) and death(p=0.002). P-/CR-POSSUM scores(n=11) showed no significant correlation with major complications or LOS. One-year survival demonstrated no correlation between P-/CR-POSSUM with OS. Conclusions: Surgical treatment of CRC showed survival benefit and should be considered for patients with low functional capacity. Due to our small sample size, P-/CR-POSSUM were not correlated with major complications, LOS and OS.